Tujuan dalam penelitian ini, untuk mendeskripsikan (1) jasa pendidikan di MTs Negeri Sukoharjo 2012/2013 (2) pemasaran jasa pendidikan (3) upaya pengembangan pemasaran jasa pendidikan - Werdiningsih, Mulyanti (2016)
This type of research is research using ethnographic approach. The experiment was conducted at MTs Sukoharjo. The main data obtained from the field of student affairs deputy headmaster, the deputy headmaster areas of the curriculum, public relations deputy headmaster, the deputy headmaster fields of infrastructure, teachers and students. Methods of data collection by interview, observation and documentation. Data were analyzed using Interactive models include data reduction, data presentation and conclusion or verification. The validity of the data using triangulation of data sources. The results showed that (1) Services 2012/2013 education includes products which learners are seen from the way of recruitment, academic and non-academic achievements,4the price of education costs met from funds DIPA and BOS, strategic location, the promotion aims to inform the madrasas, Resources human proportional number of teachers made up of civil servants and non-civil servants, the process of teaching and learning activities carried out in a programmed and scheduled, adequate infrastructure, (2) marketing services 2012/2013 education through: advertising, word of mouth information, sales promotion and marketing publications. Communications media used includes brochures, famlet, banner (3) efforts to develop marketing relationships with public services, government information by word of mouth.